Given the functions:
f(x) = x^2 - 1, g(x) = x/x + 2
Why is the followig the equation of (g o f)(x)
THe answer is x^2 - 1 / x^2 + 1
This is how I got the answer with someone's help:
Assume you forgot parenthese
g(x) = x / (x + 2)
g = x^2 - 1) / (x^2 - 1 + 2)
= (x^2 - 1)/(x^2 + 1)
Is there a simpler way to get the answer?
Thank you for any further assistance
calculus ( Is there a simpler way to get answer?) - drwls, Sunday, September 28, 2008 at 4:45pm
I can't think of a better way to do it than your example.
g(x) = x/(x+2)
g[f(x)] = (x^2-1)/(x^2-1 +2)